Signal Conditioning An Introduction to Continuous Wave Communication and Signal Processing - Das, Apurba; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
"Signal Conditioning(3y (Bis a comprehensive introduction to electronic signal processing. The book presents the mathematical basics including the implications of various transformed domain representations in signal synthesis and analysis in an understandable and lucid fashion and illustrates the theory through many applications and examples from communication systems. The ease to learn is supported by well-chosen exercises which give readers the flavor of the subject. Supplementary electronic materials available on http://extras.springer.com including MATLAB codes illuminating applications in the domain of one dimensional electrical signal processing, image processing and speech processing. The book is an introduction for students with a basic understanding in engineering or natural sciences.s
Introduction to Signal Conditioning -- Fourier Series and its application -- Fourier Transform and spectral analysis of signals -- Z-Transform -- Amplitude modulation -- Angle modulation: Frequency and Phase modulation -- Analog multiplexing and multiple access -- Random signals and noise in communication system -- Noise performance of Analog Communication systems -- Upgrading communication systems from analog to digital -- Security issues in communication: digital vs. Analog.
Keywords: Engineering; Telecommunication; Engineering; Signal, Image and Speech Processing; Communications Engineering, Networks